A Panoramic Look to Thailand: The Evolution of Thailand's Tourism Promotion (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An organization called the Tourism of Thailand was founded by Prince Purachara Jayakara, the Prince of Kamphaengphet. When sitting as a train commander, the prince sent stories about Thailand to get published in the USA. In 1924, he set up an advertising department for the State Railway of Thailand to help tourists who visited Thailand and promote Thailand among foreigners. The office was originally at the State Railway of Thailand but was later moved to Hua Lamphong Railway Station. Subsequently after Prince Purachara Jayakara went to work for the Ministry of Commerce and Transport, the office also moved there but it was still working closely with the State Railway of Thailand.